2022
DOI: 10.1177/20480040211070481
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound derived maximal systolic acceleration can be a reliable and rapid alternative to ankle brachial pressure indices for the diabetic population with lower extremity arterial disease; a prospective, observational cohort study

Abstract: Objectives: Ankle brachial pressure index (ABPI) is limited for diabetic patients. This can have costly impacts upon patient's quality of life along with healthcare budgets, with diabetic care equating to approximately 10% of NHS expenditure.11 We aimed to determine whether ultrasound waveform parameters are an alternative for quantifying lower extremity peripheral arterial disease (PAD) where ABPI is unreliable. Design: This was a prospective, observational study. Waveform parameters, systolic rise time (SRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thirty‐five studies 34‐37,39‐50,52‐62,64,65,67‐72 involving 3905 participants and 3 studies 33,38,51 including 497 limbs (number of participants not reported) investigated the ability of the ABI to identify PAD. Seven studies involving 1372 people 34,39,44,57,58,65,69 and 1 study of 89 limbs (number of participants not reported) 33 investigated the diagnostic accuracy of the TBI.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐five studies 34‐37,39‐50,52‐62,64,65,67‐72 involving 3905 participants and 3 studies 33,38,51 including 497 limbs (number of participants not reported) investigated the ability of the ABI to identify PAD. Seven studies involving 1372 people 34,39,44,57,58,65,69 and 1 study of 89 limbs (number of participants not reported) 33 investigated the diagnostic accuracy of the TBI.…”
Section: Resultsmentioning
confidence: 99%
“…For the 38 studies using the ABI as an index test, the threshold used to indicate a positive (i.e., abnormal) test varied. Nine studies used a threshold of <0.9, 38,42,54,56,59,60,70–72 8 studies used a threshold of ≤0.9, 34,39,41,43,52,53,58,64,65 7 studies use a threshold of <0.9 and >1.3, 33,46,50,55,57,61,69 2 studies used a threshold of ≤0.9 and ≥1.3, 37,40 3 studies used a threshold of <0.9 and >1.4 51,62,65 one used ≤0.9 and ≥1.4 48 and the remainder did not state a threshold. Two studies compared the diagnostic accuracy of ABI ≤0.9 and ABI ≤0.90 or >1.3/1.4 34,43 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations